The importance of organizational citizenship behaviour among hotel employees / Shaiful Annuar Khalid and Hassan Ali - Khalid, Shaiful Annuar; Alias, Hassan (Universiti Teknologi MARA, Perlis, 2006)
Given today's competitive business environment, hotels must look into new ways to improve their competitiveness. Organisational citizenship behaviour (OCB) is particularly important in the service sector such as hotels. This article proposes extra-role behaviours such as OCB, in the continuing effort to improve the quality of hotel services for customers and to enhance hotel operational efficiency. This study examines the levels of OCB among 557 employees from 63 star-rated hotels in the states of Perils, Kedah and Pulau Pinang. The results suggest that a majority of the respondents engaged in at least moderate levels of OCB. The implications of these findings for hotel operators are discussed.